A new species Phoreiobothrium gawali from Chrcharis acutus [Muller and Henle, 1906] at Bancot, Ratnagiri M.S. - Khadap, R M; Dandwate, R R (International Multidisciplinary Research Journal, 2012)
A New species of cestode Phoreiobothrium gawali was crected from the marine fish Carcharis acutus Muller & Henle,1841 (Yamaguti, 1959) collected from Bancot ( West cost of India).We have describe this new species in the genus Phoriobthrium Linton1889. We have foun P.gawali differerent from other species in body measurement, scolex length, and breadth sucker neck testes. Ovary vagins genital pore vitellaria host and locality.